Aerospace. Nuts, hexagonal, slotted (castellated), reduced height, normal across flats, with MJ threads, classifications: 450 MPa (at ambient temperature)/120°C, 450 MPa (at ambient temperature)/235°C, 600 MPa (at ambient temperature)/425°C, 900 MPa (at ambient temperature)/235°C, 900 MPa (at ambient temperature)/315°C, 900 MPa (at ambient temperature)/650°C, 1100 MPa (at ambient temperatu. (15th August 1997) - British Standards Institution,
No abstract available